2017
DOI: 10.1056/nejmoa1700456
|View full text |Cite
|
Sign up to set email alerts
|

Surgical or Transcatheter Aortic-Valve Replacement in Intermediate-Risk Patients

Abstract: TAVR was a noninferior alternative to surgery in patients with severe aortic stenosis at intermediate surgical risk, with a different pattern of adverse events associated with each procedure. (Funded by Medtronic; SURTAVI ClinicalTrials.gov number, NCT01586910 .).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

73
1,416
9
67

Year Published

2018
2018
2019
2019

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 2,419 publications
(1,647 citation statements)
references
References 20 publications
73
1,416
9
67
Order By: Relevance
“…The issue of cerebrovascular complications in the context of the TAVI procedure is well known since the first reports, and it was confirmed by the major randomized trials that compared TAVI versus surgery in high‐ and moderate‐risk patients 1, 2, 3, 4, 5, 6. These trials focused on the rate of “clinically relevant” cerebrovascular accidents and obviously prompted the ideation and introduction of EPD currently in use or under investigation.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…The issue of cerebrovascular complications in the context of the TAVI procedure is well known since the first reports, and it was confirmed by the major randomized trials that compared TAVI versus surgery in high‐ and moderate‐risk patients 1, 2, 3, 4, 5, 6. These trials focused on the rate of “clinically relevant” cerebrovascular accidents and obviously prompted the ideation and introduction of EPD currently in use or under investigation.…”
Section: Discussionmentioning
confidence: 97%
“…In the past decade, transcatheter aortic valve implantation (TAVI) triggered a paradigm shift in the treatment of patients with severe symptomatic aortic stenosis 1, 2, 3, 4, 5, 6. Nonetheless, along with groundbreaking efficacy results, data concerning the risk of cerebrovascular complications have been consistently reported in studies using either diffusion‐weighted magnetic resonance imaging (DW‐MRI) or high‐intensity transient signals as assessed by transcranial Doppler 7, 8, 9, 10.…”
mentioning
confidence: 99%
“…If transcatheter heart valve (THV) durability up to 5 years is already a well‐established reality, with low rates of structural valve dysfunction (SVD) demonstrated in large and methodologically rigorous studies,4, 5, 6, 7, 8 data on clinical outcomes and THV integrity after 5 years remain extremely scarce 9. An important challenge when reporting the rates of SVD (and comparing them with those of previous studies) deals with its definition.…”
Section: Introductionmentioning
confidence: 99%
“…Data from the registry arm of the PARTNER 2 (Placement of Aortic Transcatheter Valves) study comparing TAVR with the Sapien 3 THV with a propensity‐matched surgical cohort demonstrated both noninferiority and superiority of TAVR versus SAVR for the composite outcome of death, stroke, and moderate/severe aortic regurgitation, with overall low complication rates using this newer THV (Table 1). 13 Comparable findings were revealed in the SURTAVI (Surgical Replacement and Transcatheter Aortic Valve Implantation) trial using the self‐expanding CoreValve or Evolut R THV in intermediate‐risk patients 14. At 2 years, there was no difference in the composite outcome of all‐cause death or disabling stroke.…”
Section: Clinical Trials In Operable Patientsmentioning
confidence: 93%
“…The Sapien 3 valve features a sealing skirt, and the latest‐generation CoreValve Evolut PRO also incorporates a pericardial tissue wrap specifically designed to reduce PVL. However, the need for new PPM implantation remains the Achilles’ heel of TAVR, with 30‐day PPM rates of ≈10% for balloon‐expandable THV13 and ≈25% for self‐expanding THV14 (Table 1). In the SURTAVI trial, there was no difference in PPM rate between the CoreValve and Evolut R THV (25.5% versus 26.7%, respectively), although only 16% of patients in the study received the newer Evolut R THV.…”
Section: Potential Limitations Of Tavr In Operable Patientsmentioning
confidence: 99%